ANALISIS ETIKA PROFESI LINGKUNGAN PRAKTIKUM TEKNIK INFORMATIKA UNIVERSITAS PALANGKA RAYA - Hariz Kurniawan; Depro Winoto; Cyaramani Cyaramani; Jadiaman Parhusip (LPPM Politeknik Pratama Kendal, 2024)
This study aims to explore the implementation of professional ethics in the Informatics Engineering practicum at Universitas Palangka Raya. A descriptive qualitative approach with a case study design was employed, involving interviews, observations, and an analysis of practicum guidelines. The findings indicate that while students have a basic understanding of professional ethics, such as responsibility toward users and data integrity, their deeper understanding of applying ethics within the practicum context remains limited. Supervision of ethics implementation presents a significant challenge, with violations such as tardiness and dishonesty in reporting observed. However, group discussions on ethical challenges indicate positive efforts to raise ethical awareness among students. This study recommends strengthening the socialization of professional ethics throughout the education process, enhancing supervision, and updating practicum guidelines by incorporating ethical decision-making simulations in various practicum scenarios.